Representações das cotas raciais na graduação e pós-graduação entre docentes produtividade em pesquisa (PQ) na Universidade Federal de Goiás - Santos, Aline David dos (2018)
In the last decades, studies developed on higher education in Brazil have demonstrated there is still a need to expand the access to that educational level. Taking into account a racial clipping, the postgraduate level of education is a reflection of the graduation level: in both the number of black students is low; in postgraduate studies there is an even smaller proportion of them. Social and racial quotas for access to graduation in higher education have existed since the first decade of the 2000s and have gained strength as implemented public policy especially in 2012, with the outcome of the Quotas Law – Law 12.711/2012. At the postgraduate level, vacancy reservations began to take place over the last years, but experiences were restricted to some sparse university courses. The most comprehensive initiative is the one posed by the Federal University of Goiás (UFG), which has established a quota rule for all its postgraduate courses. This research proposes a study of the considerations of professors working in such programs at UFG, focusing on those who are considered the exponents of research and academic production, named as Productivity-in-Research Professors (PQ). By using descriptive research methodology, with semi-structured interview techniques we will try to present these social representations and perceive support, resistance, redirecting and redefinitions towards such public policies. The work’s objective is to identify the degree of acceptance or resistance with regards to the racial quotas policy in graduate and postgraduate studies among the PQ professors.